2017
DOI: 10.1038/s41598-017-07101-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of lung macrophage subpopulations in COPD patients and controls

Abstract: Lung macrophage subpopulations have been identified based on size. We investigated characteristics of small and large macrophages in the alveolar spaces and lung interstitium of COPD patients and controls. Alveolar and interstitial cells were isolated from lung resection tissue from 88 patients. Macrophage subpopulation cell-surface expression of immunological markers and phagocytic ability were assessed by flow cytometry. Inflammatory related gene expression was measured. Alveolar and interstitial macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 62 publications
10
80
1
Order By: Relevance
“…CMPs integrate in the toponome, which combines aspects of the proteome and the interactome, and this study reflects the assembly and/or interactions of the 13 markers in a given cellular space in intact cells. As pointed out in the Background, the AM cell population is known to have a high degree of phenotypic diversity [12,31,32,50]. Hence the finding of heterogeneity identified in this study is, in itself, not surprising.…”
Section: Discussionsupporting
confidence: 68%
“…CMPs integrate in the toponome, which combines aspects of the proteome and the interactome, and this study reflects the assembly and/or interactions of the 13 markers in a given cellular space in intact cells. As pointed out in the Background, the AM cell population is known to have a high degree of phenotypic diversity [12,31,32,50]. Hence the finding of heterogeneity identified in this study is, in itself, not surprising.…”
Section: Discussionsupporting
confidence: 68%
“…IM showed a lower expression of tumor-promoting genes such as Mmp9 33 and immunomodulatory mediators (Arg1, Nos2). Hence, neutrophil infiltration might link some of the alterations reported on lung tumor patients' AMs [34][35][36] . Finally, treating KP mice with anti-Ly6G ab alone failed to demonstrate any effect on tumor growth and the immune signature.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, cigarette smoke reportedly increased the accumulation of CX3CR1 + CD11b + mononuclear phagocytes that are spatially confined to the lung interstitium, and mice deficient for CX3CR1 showed protection from emphysema formation (35), suggesting the important role of IMs in smoke-induced COPD as well. Intriguingly, gene expression profiling in lung samples isolated from COPD patients revealed that IMs display a higher proinflammatory signature than AMs (36), suggesting the possible role of IMs rather than AMs in the pathogenesis of human COPD as identified in the mouse model.…”
Section: Discussionmentioning
confidence: 98%